Flexural Strengthening of Reinforced Concrete Beams using NSM GFRP: Assessing Key Parameters - Arab, Berlant (AUC Knowledge Fountain, 2025)
The structural integrity and longevity of Reinforced Concrete (RC) beams are critical to modern construction, influencing safety, usability, and maintenance costs over time. As civil engineering endeavors to meet the challenges posed by aging infrastructure and evolving usage demands, rehabilitating and strengthening RC structures have become essential practices globally. This research focuses on a prevalent yet innovative method of enhancing RC beams: the application of Near Surface Mounted (NSM) Glass Fiber Reinforced Polymer (GFRP) bars. GFRP is increasingly favored in structural engineering due to its superior properties to traditional materials. These include high tensile strength, resistance to corrosion, lightweight nature, and long-term durability. Among various reinforcement techniques, the NSM application of FRP stands out. This method involves embedding FRP bars or strips within grooves cut along the tension side of concrete beams. This technique not only enhances flexural strength but also preserves much of the original structural aesthetics and integrity. The core objective of this research was to comprehensively understand how various parameters affect the flexural strengthening capacity of RC beams strengthened with NSM GFRP bars. An experimental program was designed, encompassing testing of twenty-two RC beams under controlled conditions to isolate and evaluate the impact of several key factors: the diameter of GFRP bars, their bonding length, the number of bars used, the techniques employed to enhance bond strength, the placement of bars within the concrete matrix, and the type of groove-filler material utilized in the grooves. The research’s findings highlight the critical nature of GFRP bar diameter and bonding length in enhancing beam performance. Specifically, larger bar diameters (12 mm and 16 mm, adopted herein) significantly increased the beams' load capacity, demonstrating a clear correlation between bar size and structural resilience. Conversely, smaller diameters (8 mm) were less effective, offering minimal improvements, which underscores the need for appropriate sizing in planning retrofit projects. Bonding length emerged as another crucial factor, with results showing that beams adhering to the American Concrete Institute’s (ACI) recommended bonding lengths could fully utilize the GFRP bars’ tensile strengths. Inadequate bond lengths led to reduced load capacities and sudden failures, emphasizing the importance of precise calculations and adherence to established guidelines. The study also explored the effects of increasing the number of GFRP bars. While intuitively thought to improve strength, the benefits were marginal when the bond lengths were not optimized, suggesting that the quality of installation often outweighs quantity in composite reinforcement. Furthermore, the research investigated bond enhancement techniques such as mechanical anchoring and the use of epoxy groove-filler. These methods were found to improve bond strength and delay failure modes, yet they could not fully compensate for the deficiencies in bonding length. The NSM technique, which incorporates additional mechanical or adhesive interventions, provided slight performance improvements. However, the ultimate efficacy of beam strengthening remained heavily contingent on correct adherence to bonding specifications. In conclusion, this study not only substantiates the efficacy of NSM GFRP bars in enhancing the flexural performance of RC beams but also delineates the critical parameters that govern the success of such interventions. The insights garnered here pave the way for further research into refining bonding length equations and enhancing predictive modeling through advanced techniques like numerical (finite element) analysis. This will enable engineers and designers to more accurately predict outcomes and design more effective RC beam strengthening strategies, ultimately leading to safer, more durable structures.